Supplementation of two corn sources in calves at San Alberto, Cesar - Galán, Jorge Alejandro; Herrera Larotta, Laura Cristina; Pabón, Carlos Fernando (Spei Domus, 2011)
This research was carried out at Las Trucas Farm in San Alberto (Colombian department Cesar) aiming to assess, both nutritionally and economically, two alternative supplements corresponding to raise suckling grazing calves in order to monitor efficiency of hydroponic process for corn seed (chm) and its yield. The elements employed to develop this assessment were a hydroponics infrastructure, a hand-operated mill, Creole corn seed, and a sample of 15 male suckling calves, divided in 3 groups of 5 replications each where T1 corresponds to a control group, T2 was a group supplemented with a 30% of chm regarding the consumption based on 12% of live weight, and T3 was a group supplemented with hominy grits (mm) equivalent to dry matter provided by T2. The corn seed got 92% of germination with a conversion index of 4,18 kg of chm per each kilogram of sown seed. Regarding chemical analysis, the dry matter of chm was 16% and 86% for mm. Crude protein 10,5% forchm and 9,3% mm. Covariance analysis was used with no significant difference among treatments (P>0,2). Once information examined, average weight gain for groups was as follows: 453 grams per day for T1, T2 got 520 grams per day and 458 grams per day for T3. The body condition score of the supplemented animals was improved by 3,5 in case of chm; 3 for mm; and 2,5 for the control group.